The Glasgow Naturalist 2020
DOI: 10.37208/tgn27301
|View full text |Cite
|
Sign up to set email alerts
|

When to count? Indices of population size for mountain hares of the north-west Lammermuir Hills, Scotland

Abstract: Surveys with binoculars at two different times of day and in various months of the year, along with camera trap studies of diel activity patterns, were used to inform an appropriate period to count mountain hares ( Lepus timidus) on managed red grouse (Lagopus lagopus ) moorland of the Lammermuir Hills, south-east Scotland. Factors affecting the numbers of hares counted were time relative to sunrise, the presence of winter coat colour and reproductive behaviour in spring. Counts of hares in March and April sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…That said, we had deliberately chosen those areas for survey efficacy. By contrast, in mountain hare surveys on the Scottish Lammermuir hills, Pettigrew ( 2020 ) recommended 90‐min surveys by dawn light as hares are more active and visible at this time rather than by midday when dormant. However, this suggestion lacked information regarding imperfect detection process or detection probability so is hard to compare; and those surveys occurred on small accessible areas ~26 km 2 of relatively flat elevation 420–520 m. By contrast, the Peak District required >120 km of transects and featured steep hills elevation 630 m with transect elevation changes >350 m over 1 km.…”
Section: Discussionmentioning
confidence: 99%
“…That said, we had deliberately chosen those areas for survey efficacy. By contrast, in mountain hare surveys on the Scottish Lammermuir hills, Pettigrew ( 2020 ) recommended 90‐min surveys by dawn light as hares are more active and visible at this time rather than by midday when dormant. However, this suggestion lacked information regarding imperfect detection process or detection probability so is hard to compare; and those surveys occurred on small accessible areas ~26 km 2 of relatively flat elevation 420–520 m. By contrast, the Peak District required >120 km of transects and featured steep hills elevation 630 m with transect elevation changes >350 m over 1 km.…”
Section: Discussionmentioning
confidence: 99%
“…The general topography of the study area, the pattern of muirburn (Yallop et al., 2006), and the location of camera traps are shown in Figure 1b. During mountain hare surveys (Pettigrew, 2020), up to 20 individual hares have been routinely counted by the Lammermuir Hare Group in the camera study area.…”
Section: Methodsmentioning
confidence: 99%
“…The general topography of the study area, the pattern of muirburn (Yallop et al, 2006), and the location of camera traps are shown in Figure 1b. During mountain hare surveys (Pettigrew, 2020), up to…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation